2014
DOI: 10.1002/jms.3334
|View full text |Cite
|
Sign up to set email alerts
|

Protonated primary amines induced thymine quintets studied by electrospray ionization mass spectrometry and density functional theory calculations

Abstract: As the novel magic number clusters of nucleobases, the thymine quintets induced by ammonium ion (NH4(+)), and particularly by its derivatives such as protonated alkyl amines and protonated aryl amines, have been studied by electrospray ionization mass spectrometry (ESI-MS) and density functional theory (DFT) calculations. The DFT-optimized geometry of NH4(+) induced thymine quintet ([T5 + NH4](+)) reveals some new features including three additional hydrogen bonds between NH4(+) and its surrounding thymine mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…S4 †), which is in accordance with the previously reported quintet cluster of thymine induced by the protonated amines. 26 But remarkably, no high-order magic number clusters of thymine (n $ 15) were observed. This is probably due to the fact that the high-order magic number clusters need more than one positively charged center to stabilize the structure, in accordance with our previous report that the doubly charged 15-mer ([T 15 + 2M] 2+ ) is stabilized by two metal ions.…”
Section: The High Specicity Of Forming the Magic Number Cluster Towa...mentioning
confidence: 99%
See 2 more Smart Citations
“…S4 †), which is in accordance with the previously reported quintet cluster of thymine induced by the protonated amines. 26 But remarkably, no high-order magic number clusters of thymine (n $ 15) were observed. This is probably due to the fact that the high-order magic number clusters need more than one positively charged center to stabilize the structure, in accordance with our previous report that the doubly charged 15-mer ([T 15 + 2M] 2+ ) is stabilized by two metal ions.…”
Section: The High Specicity Of Forming the Magic Number Cluster Towa...mentioning
confidence: 99%
“…In fact, many studies have been reported on the self-clustering of nucleobases. [18][19][20][21][22][23][24][25][26] In these previous reports, thymine can aggregate to form the magic number clusters in the presence of alkali metal ions or an ammonium cation through non-covalent interactions. [22][23][24] In other words, these magic number clusters enable the small target ions such as Na + , K + and NH 4 + to be detected by MS through a "mass-shi" to the higher mass range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies by our group, 11,12,19,20 have demonstrated that alkali metal ions or primary amine induced thymine (or analogs) were thermodynamically stable and can be detected by ESI-MS or DESI-MS. Tertiary amines were not able to induce such clusters, probably because the cavity in the thymine (or analogs) circle was too small to entrap the charged moiety in tertiary amines.…”
mentioning
confidence: 99%
“…2c and d To explain the different behaviours in the cluster formation, theoretical calculations were made to study the relative stabilities of the clusters formed by thymine with 1,3-PDA and 1,2-PDA, respectively. The possible structures were proposed according to a previously established model, 11,12,19,20 in which 5 or 6 thymine molecules were arranged into circles via double complementary hydrogen bonds, and the circles entrapped the nitrogen charge centres. Schalley et al 21 have used molecular dynamics to calculate model structures of organometallic clusters formed in ESI-MS, and we applied similar theoretical methods in our study.…”
mentioning
confidence: 99%